Sita Harta Suami Sebagai Jaminan Nafkah Anak Pasca Cerai: Perspektif Maqasid al-Syari’ah dan Perlindungan Anak - Ulfa Fauziah Hidayati; Mesraini; Rosdiana (UIN Syarif Hidayatullah Jakarta, 2026)
This study analyzes the mechanism of asset seizure against ex-husbands as a guarantee for child maintenance after divorce under Supreme Court Circular Letter (SEMA) No. 5 of 2021 and examines it from the perspective of Maqasid al-Syari’ah. The research employs a normative-empirical method by analyzing relevant statutory regulations and empirical data obtained through in-depth interviews with judges at Religious Courts in the Special Capital Region of Jakarta. The location was selected due to its high divorce rate and socio-economic complexity, which represent national legal practices. The findings reveal that asset seizure functions as an ultimum remedium when child maintenance obligations are not voluntarily fulfilled after a final court decision. However, its implementation remains limited due to low legal awareness among former wives and technical obstacles in asset identification and execution.